USING DIGITAL EDUCATION TECHNOLOGIES IN UZBEKISTAN - Iroda Gayratovna Majidova (Bright Mind Publishing, 2025)
The rapid advancement of digital technologies has significantly transformed the education sector worldwide, including Uzbekistan. With the implementation of the "Digital Uzbekistan 2030" strategy, digital tools have become an essential component of modern educational practices, fostering interactive learning, accessibility, and personalized education. This paper explores the role of digital technologies in education, focusing on their impact on teaching methodologies, student engagement, and overall academic performance. The study highlights key digital tools such as Learning Management Systems (LMS), artificial intelligence (AI)-based applications, and virtual learning environments (VLEs), which enhance the efficiency of education delivery. Moreover, the paper discusses the challenges faced by the education system in adopting digital technologies, including digital literacy, infrastructure development, and cybersecurity concerns. The findings indicate that digital technologies not only improve the quality of education but also contribute to lifelong learning opportunities and the global competitiveness of students. By integrating digital tools effectively, Uzbekistan can enhance its education system to align with global standards and meet the demands of the digital economy.
Keywords: Digital education, Learning Management Systems, virtual learning, artificial intelligence in education, student engagement, Digital Uzbekistan 2030, e-learning platforms, digital transformation, academic performance.